The Impact of Best HR Practices and Employee Engagement on Career Success: A Discriminant Analysis - Nageswara Rao, R.; Vani, H.; Meesala, Appalayya (Prabandhan: Indian Journal of Management, 2015)
Purpose: Best HR practices and employee engagement are the most popular mantras for high organizational performance, which are believed to first raise the morale and energy level of the employee, and later are to be followed by the spirited discretionary employee effort. In fact, engagement is a part of best HR practices, which is an umbrella concept. However, the intriguing question is: Do all these practices aimed at improving organizational performance make for individual employee's career success, which is the most powerful driving force behind an employee's performance? This research is an attempt to fathom out which factors contribute most to career success of an employee: Best HR practices or employee engagement or performance? Design and Methodology: A survey was done on 206 employees working in different organizations in Andhra Pradesh, and a discriminant analysis (DA) was conducted to find out which factors contributed most to the career success of the employees. Original Contribution: This research establishes a link between career success , engagement efforts, and best HR practices. Findings: The results show that engagement contributes most to career success followed by best HR practices. Job performance has a doubtful role in determining career success. Originality and Value: Organizations engaged in vigorous implementation of best HR practices would realize from this research that engagement efforts are better than best HR practices from the standpoint of an employee's career success. Practical Implications: Engagement efforts, which are employee-centered, are the best bet than best HR practices, which are firm-centered.